REFLECTIONS ON THE COUNTABLE PRACTICE IN PERÚ - Urbano Ventocilla, César (2010)
The article present to make them reflect on the accounting practice in Peru. We finished the first decade of this new century and our accounting profession, as Peter Drucker would say, has been characterized by constant change has been suffering, to such a degree that now seems that we are in new paradigms. And most importantly, the future of our practice is seen reflected constant changes, among others, due to the speed at which technology is changing the information, the need for continuing education, accreditation of having renewables, way to interact with senior management, doing business in globalized environments and manage organizations that constantly reinvent themselves. Yes to this environment in which accounting practice is developed in Peru we add the misperception that young people today have college-age Lima on the accounting profession and the various issues we have to solve the union level and the various regulatory bodies the accounting profession in our country. And if we add to this the training of future accountants in universities is not the one actually calls this changing market. Everything described above poses a great challenge, in which all of us, public accountants, regulators of the practice of accounting in our country, including the Peruvian universities have to reinvent the accounting profession to change that perception and make accountants continue to be considered by the business community as its Strategic Partner Organizations, characterized by creating value in organizations where they offer their professional services.